Effectiveness of Zakat as Tax Deduction in Muara Enim Baznas - Fitriya, Ussy; Supriadi, Supriadi (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Zakat, a fundamental Islamic obligation, has the potential to be utilized as a tax deduction to increase zakat fund collection. Despite regulations permitting zakat as a deductible expense, the actual implementation and awareness among Muslim taxpayers remain suboptimal. In Indonesia, the collection of zakat is significantly lower than its potential, indicating issues in management and understanding. This study aims to evaluate the mechanism and effectiveness of zakat as a taxable income reduction in increasing zakat funds at the Muara Enim Regency BAZNAS. A descriptive qualitative approach was employed, involving field research through documentation, observation, and interviews. The population comprised Muslim taxpayers, tax officials, and zakat administrators selected using purposive sampling. Data analysis focused on the implementation process and its impact on zakat revenue. The findings reveal that the zakat deduction mechanism in Muara Enim is not effectively increasing zakat revenue. Challenges include complicated procedures and limited taxpayer understanding regarding zakat calculations as a tax deduction. Consequently, the utilization rate of zakat as a tax deduction remains low. To optimize zakat collection through tax deductions, efforts should focus on simplifying procedures and improving taxpayer awareness and understanding. Enhancing these aspects can potentially increase zakat revenue, supporting the socio-economic development of Muara Enim.